Tear Film Status in Patients Attending the Eye Clinic in South Sharqiya Region - Keshav, Belur R (OMJ, 2007)
OBJECTIVE: To study the tear film profile of patients attending the eye clinic of Sur hospital of South Sharqiya region of Oman and to study the epidemiology of patients having abnormal tear film profile. METHOD: Patients attending the eye clinic of Sur hospital and B. Ali eye clinic were asked about the clinical symptoms relevant to dry eye and subjected to tear film tests namely TBUT (Tear Break up Time) and Schirmer’s 1 to assess tear film profile. Patients with irregular corneas were excluded from the study. Overall 127 patients were included in the study. RESULTS: 42.5% (95% CI: 33.9% to 51.1%) of patients examined had abnormal tear film profile with patients >30 years 56.75% (95% CI: 45.4% to 68%) showing abnormality more often and females 40.3% (95% CI: 29.3% to 51.2%) outnumbered males. Burning was the main symptom in patients with abnormal tear film profile. CONCLUSION: We infer that a large number of patients had abnormal tear film profile most of them were asymptomatic and trachoma figured prominently amongst the diseases in cases with abnormal tear film profile.